PERENCANAAN SISTEM DRAINASE DAN TROTOAR Studi Kasus : Lingkungan Kelurahan Banjaran Kota Kediri - Romadhon Romadhon; Moch Zaenuri; Herlan Pratikto (U Karst, 2019)
Drainage channels to drain the wastewater is dirty water from households and from the rain. The purpose of this drainage planning is to plan the dimensions calculated channels after knowing the rainwater discharge and discharge dirty water from households that must be accommodated in the channel. After the dimensions sufficient to drain off rainwater or dirty water then it will not overflow of water or flood occurred at a time when it was raining. The data used to plot this drainage is complete with the topography situation maps used for planning the direction of flow. Further rainfall data from three stations for 20 years who later tested the consistency, test its homogeneity. Debit calculated on the basis of high average rainfall with a rational method of Q = 0.2778 x C x I x a. Then calculated Komulatif discharge (Discharge rainwater + wastewater discharge citizens) to plan the drainage channels. Discharge of Komulatif then calculated dimensions of its channels with Manning formulas, namely: Q = 1/n x R ^ (2/3) x S ^ (1/2) x a. Of the map data and topographic situation obtained the type size of the funnel and after is calculated with a formula of Manning gained square dimensions: b = 0.80 m and h = 0.10 m. in addition also obtained the protection of 0.70 m high, then from the dimensions calculated Plan Cost budget (RAB) amounting to Rp. 2,929,983,000.00. After the survey and design of pavement, designed using the width and height dimensions of 1.10 m sidewalk 0.20 m. using the cover stone-lined Ditch U-Andhesit 20x40, floor tile Line 30x30 for disabled pedestrians disability, brush/stone ampyang for Iron Manhole 70x70 fastener. Keywords: Drainage System, Water Debit, Method CalculationSaluran drainase untuk mengalirkan air limbah adalah air kotor dari rumah tangga dan dari hujan. Tujuan dari perencanaan drainase ini adalah untuk merencanakan dimensi saluran yang dihitung setelah mengetahui debit air hujan dan debit air kotor dari rumah tangga yang harus ditampung di saluran tersebut. Setelah dimensi cukup untuk mengalirkan air hujan atau air kotor maka tidak akan meluap air atau banjir terjadi pada saat hujan. Data yang digunakan untuk merencanakan drainase ini lengkap dengan peta situasi topografi yang digunakan untuk merencanakan arah aliran. Selanjutnya data curah hujan dari tiga stasiun selama 20 tahun yang kemudian menguji konsistensi, menguji homogenitasnya. Debit dihitung berdasarkan curah hujan rata-rata tinggi dengan metode rasional Q = 0,2778 x C x I x a. Kemudian dihitung debit Komulatif (debit air hujan + debit air limbah warga) untuk merencanakan saluran drainase. Pelepasan Komulatif kemudian dihitung dimensi salurannya dengan rumus Manning, yaitu: Q = 1 / n x R ^ (2/3) x S ^ (1/2) x a. Dari data peta dan situasi topografi diperoleh ukuran jenis corong dan setelah dihitung dengan rumus Manning diperoleh dimensi persegi: b = 0,80 m dan h = 0,10 m. selain itu juga didapat perlindungan setinggi 0,70 m, kemudian dari dimensi yang dihitung anggaran Biaya Rencana (RAB) sebesar Rp. 2,929,983,000.00. Setelah survei dan desain trotoar, dirancang menggunakan dimensi lebar dan tinggi 1,10 m trotoar 0,20 m. menggunakan penutup batu Ditch U-Andhesit 20x40 berlapis, ubin lantai Line 30x30 untuk cacat pejalan kaki cacat, sikat / batu ampyang untuk pengikat Iron Manhole 70x70.Kata Kunci: Sistem Drainase, Debit Air, Metode Perhitungan